MANGROVE SPECIES DIVERSITY IN ARIYANKUPPAM ESTUARY, PUDUCHERRY, INDIA - Silpa.P & Dr.T. Ramanathan* (Chelonian Research Foundation, 2024)
True mangrove species and associate mangrove species are the two categories into which the plant life in a mangrove habitat is divided. While associated species are present in both the mangrove ecosystem and its environs, true mangrove species are exclusively found in mangrove wetlands. There are 69 plant species recognized to be true mangroves worldwide. The present study aim to find out the true mangrove diversity in Ariyamkuppam, Puducherry. Six true mangrove floral species from three families, three orders, and the same class were recorded. One true mangrove was threatened Species in IUCN Red data book.